Convergences between national and South American public policies for the promotion of books, reading, and libraries and 2030 Agenda SDG 4: what is behind them? - Camillo, Everton da Silva [UNESP]; Castro Filho, Claudio Marcondes de [UNESP] (Univ Federal Santa Catarina, 2020)
Objective: To identify and to measure existing convergences between national public policies of promotion of the books, reading and libraries goals of South American countries, and the ten goals of 2030 Agenda Sustainable Development Goal (SDG) 4 (Quality Education). Methods: Content Analysis method was used to objectify the investigation, and the thematic analysis technique was applied. Results: The public policies analyzed are closely linked to the area of education. It is understood that training professionals for the labor market are not an action that is at their core. It is also understood that the analyzed public policies favored basic education and relegated the prospects for secondary and tertiary education in the South American countries, to which the analyzed national public policies belong. Conclusions: It is concluded that, regarding the forces, the analyzed public policies are strongly linked to the actions of education and its fomentation in society. They also privilege the primary education and, as it is understood in the analysis, some pedagogical practices. However, the perceived weaknesses in the outcome relate to secondary and tertiary education. The national public policies analyzed are far from the goal of searching for competences and specific skills for the labor market, linked to technical and vocational education.
Keywords: Public Policies; Promotion of book; reading; library; SDG 4; 2030 Agenda; South America